2012
DOI: 10.3998/ark.5550190.0013.315
|View full text |Cite
|
Sign up to set email alerts
|

Thianthrene-based oligomers as hole transporting materials

Abstract: The thianthrene-arylene conjugated units have been designed and synthesized via Suzuki or Stille coupling reaction. The structures and properties of the synthesized compounds were characterized by 1 HNMR, 13 CNMR, MS, UV-Vis absorption spectroscopy, fluorescence spectroscopy as well as electrochemical measurements. The luminescent studies demonstrate that thianthrenes are good chromophores. Also the electrical properties of obtained films confirm the applicable potential of these novel aryl-based π-conjugated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Also, the HOMO is localized mostly on the carbazole moiety, suggesting a stronger electron-donating property of this unit relatively to thianthrene. This is consistent with the electrochemical characteristics of the molecule (Figure S12) indicating nonreversibility of the oxidation process as typically for carbazole. , HOMO located on the thianthrene would result in a reversible oxidation cycle. , LUMO is on the other hand situated on the thianthrene moiety.…”
Section: Resultssupporting
confidence: 86%
“…Also, the HOMO is localized mostly on the carbazole moiety, suggesting a stronger electron-donating property of this unit relatively to thianthrene. This is consistent with the electrochemical characteristics of the molecule (Figure S12) indicating nonreversibility of the oxidation process as typically for carbazole. , HOMO located on the thianthrene would result in a reversible oxidation cycle. , LUMO is on the other hand situated on the thianthrene moiety.…”
Section: Resultssupporting
confidence: 86%
“…Organic semiconductors are divided into two main classifications: low molecular weight compounds and polymers. Both categories have a common property which is the presence of a conjugated system of πbond formed from P-orbitals of carbon atoms of trigonal hybridization [15,21,22]. Following the literature, polyaniline (PANI), pentacene, poly (3-hexylthiophene) (P3HT), poly (3-alkylthiophene) (P3AT), and poly (3-octylthiophene) (P3OT) are the most commonly used OSCs in OFET technology [23].…”
Section: Introductionmentioning
confidence: 99%
“…This area of work was initially revived in 2017 by the group of Dias with the characterization of bis-thianthrenes 121 and 122 , 117 which were previously synthesized by Sołoducho and co-workers (Figure 6 ). 118 Dias and colleagues reported that all compounds exhibited RTP in the solid state, with phosphorescence contributing to >90% of the photoluminescence of certain derivatives. 117 Phosphorescence quantum yields of up to 0.42 were recorded.…”
Section: Application Of 14-dithiins and Thianthrenes In Materialsmentioning
confidence: 99%
“…Figure 5Thianthrene-containing compounds with redox-dependent conformation(114 and 115), known to bind other compounds(116)(117)(118), and participate in self-assembly(119 and 120) …”
mentioning
confidence: 99%